Effects of Task-Technology Fit and Information Technology Utilization on The Individual Performance of Employees among Industrial Manufactures in Batam - Hendra Gunawan (JURNAL INTEGRASI, 2010)
Researches analyzing the relationship between information system and individual performance are grouped into two researches, streams focusing on task-technology fit and focusing on information technology utilization. The present research aimed to empirically examine part of model technology-to-performance chain as combination of two researches streams proposed by Goodhue and Thomson (1995) to obtain better knowledge on the relationship between information system and individual performance. Various researches conducted have provided inconsistent results. Based on the problem, this research tried to re-examine the effects of task-technology fit and information technology utilization on the individual performance of employees among industrial manufactures in Batam. Model examined in this research exploited multiple regression analysis. Testing results indicated that out of 104 researches collected through survey technique among industrial manufacture employees in Batam, it was indicated that task-technology fit significantly influenced the individual performance of manufacturing employees in Batam. However, research results were not able to prove that information technology utilization provided significant influences on the individual performance of employees among industrial manufactures in Batam.